Risk Premia and Variance Bounds. - Balduzzi, Pierluigi; Kallal, Hedi (Journal of Finance, 1997)
If a pricing kernel assigns a premium to a risk variable that differs from the one assigned by the minimum-variance admissible kernel, then the pricing kernel must exhibit more variability than the minimum-variance kernel. Based on this intuition, the authors derive a variance bound that is more stringent than that of Lars Peter Hansen and Ravi Jagannathan (1991). When the authors apply their bound to the kernel of a representative consumer with power utility, they find that the consumption risk premium increases the severity of the 'equity-premium puzzle' of Rajnish Mehra and Edward C. Prescott (1985).